2023
DOI: 10.3389/fcvm.2022.1097229
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection predicts larger infarct volume in patients with acute ischemic stroke

Abstract: Background and purposeAcute ischemic stroke (AIS) is a fearful complication of Coronavirus Disease-2019 (COVID-19). Aims of this study were to compare clinical/radiological characteristics, endothelial and coagulation dysfunction between acute ischemic stroke (AIS) patients with and without COVID-19 and to investigate if and how the SARS-CoV-2 spike protein (SP) was implicated in triggering platelet activation.MethodsWe enrolled AIS patients with COVID-19 within 12 h from onset and compared them with an age- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In this meta-analysis, in those patients who had preexisting coronary artery disease, the odds ratio (OR) for the acute cerebrovascular disease was 43.12 (95% CI 1.61–6.02). Preexisting cardiovascular risk factors also predispose to an ischemic stroke in patients with COVID-19 as found in a large multiethnicity registry study and a meta-analysis [44,45]. In addition, the prognosis of stroke is worse in patients with COVID-19 [46–48].…”
Section: Ischemic Strokementioning
confidence: 93%
“…In this meta-analysis, in those patients who had preexisting coronary artery disease, the odds ratio (OR) for the acute cerebrovascular disease was 43.12 (95% CI 1.61–6.02). Preexisting cardiovascular risk factors also predispose to an ischemic stroke in patients with COVID-19 as found in a large multiethnicity registry study and a meta-analysis [44,45]. In addition, the prognosis of stroke is worse in patients with COVID-19 [46–48].…”
Section: Ischemic Strokementioning
confidence: 93%
“…COVID-19 patients hospitalized at the time of the infection have a subsequent higher risk of stroke during the follow-up compared to those non-hospitalized (Zuin et al 2023a). Moreover, a recent study demonstrated that COVID-19 extends the infarct volume during acute ischemic stroke (De Michele et al 2023). COVID-19-related ischemic stroke may occur in all age groups and predominantly in males.…”
Section: Ischemic Strokementioning
confidence: 99%
“…There is increasing evidence that COVID-19 is associated with ischemic stroke (Finsterer et al 2022;Ozcan et al 2023;De Michele et al 2023). An increasing number of COVID-19 patients with ischemic stroke have been reported (Luo et al 2022;Zuin et al 2023a).…”
Section: Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…This leads to endothelial dysfunction, characterized by impaired vasodilation, increased vascular inflammation, and a prothrombotic state [93]. This dysfunction is a critical factor in the development of various acute conditions [35,94,95], etc., and it can further exacerbate OS itself, creating a vicious cycle [96].…”
Section: Mitochondrial Imbalance and Endothelial And Mitochondrial Dy...mentioning
confidence: 99%